Pelatihan Peningkatan Kapasitas Pengelolaan Data ASN bagi Pegawai BKD PPSDM Lombok Barat - Ramdani, Rizal; Irmawan, Ifan; Bukran, Bukran (CV. Global Cendekia Inti, 2025)
This community service activity aims to enhance the capacity for managing civil servant data among employees of BKD PPSDM Lombok Barat. The program focused on equipping participants with essential skills in data processing, accuracy improvement, and the utilization of data management to support efficient governance and human resource administration. The training was initiated in response to common challenges faced by regional agencies, such as inconsistent data management practices, limited technical knowledge, and the growing demand for accurate and integrated civil servant data. As a solution, the organizing team designed a capacity-building training program specifically tailored for BKD PPSDM staff. The training taught basic and advanced skills in data management, such as checking data accuracy, using Microsoft Excel for data processing, and keeping data safe and secure. A total of 20 employees from various divisions of BKD PPSDM Lombok Barat participated in the program. In addition to expert-led sessions, the training involved hands-on practice and group discussions to strengthen technical understanding and collaborative problem-solving. As a result of this program, participants demonstrated improved technical competence, increased confidence in managing civil servant data, and a stronger commitment to maintaining data quality standards, which are crucial for supporting transparent and effective public service delivery.